Initial investigation of individual and combined annulus fibrosus and nucleus pulposus repair ex vivo. (1st September 2017) - Sloan, Stephen R.; Galesso, Devis; Secchieri, Cynthia; Berlin, Connor; Hartl, Roger; Bonassar, Lawrence J.
Graphical abstract: Abstract: Novel tissue engineered and biomaterial approaches to treat intervertebral disc (IVD) degeneration focus on single aspects of the progressive disease and hence are insufficient repair strategies. In this study, annulus fibrosus (AF) and nucleus pulposus (NP) biomaterial repair strategies were used individually and combined to treat IVD degeneration modeled in ex vivo rat-tail motion segments by annulotomy and nucleotomy. An injectable riboflavin cross-linked high-density collagen gel patched defects in the AF, while NP repair consisted of injections of a modified hyaluronic acid (HA) hydrogel. Qualitative imaging showed the annulotomy and nucleotomy successfully herniated NP material, while the HA NP injections restored intact NP morphology and the collagen AF patches sealed AF defects. Assessed by quantitative T2 magnetic resonance imaging, combined repair treatments yielded disc hydration not significantly different than intact hydration, while AF and NP repairs alone only restored ∼1/3 of intact hydration. Mechanical testing showed NP injections alone recovered on average ∼35% and ∼40% of the effective instantaneous and equilibrium moduli. The combined treatment comprising biomaterial AF and NP repair was effective at increasing NP hydration from NP repair alone, however HA injections alone are sufficient to improve mechanical properties. Statement of Significance: Intervertebral disc degeneration affects an estimated 90% of individuals throughout their life, and is a candidate pathology for tissue engineered repair. The current standard of clinical care reduces spinal articulation and leads to further degeneration along the spine, hence great interest in a regenerative medicine therapy. Literature studies focused on biomaterial repair strategies for treating degenerated discs have partially restored native disc function, however no studies have reported the use of combined therapies to address multiple aspects of disc degeneration. This initial investigation screened injectable biomaterial repair strategies ex vivo, and through complementary outcome measures showed a combined therapy restores disc function better than individual approaches. This study is the first of its kind to address multiple aspects of disc degeneration, using clinically-oriented biomaterials in a well-established animal model.